PERBEDAAN DISIPLIN KERJA PADA JENIS PEKERJAAN DI RSUD Dr MOEWARDI SURAKARTA - Marlindawati, Nino (Transformasi, 2017)
Methods This research is explanatory with quantitative approach. The population in this study,doctors, nurses and administrative staff General Hospital (Hospital) Dr. Moewardi.The resultsof the manual tabulation of the data can be seen that each of the data results of thequestionnaire study on the discipline of work based on the type of work that doctors, paramedicsand administrative staff have differences.Keywords: Work Discipline, Occupation